The role of (in)visibility in hate crime targeting transgender people. (April 2022) - Colliver, Ben; Silvestri, Marisa
This article explores incidents of hate crime targeted at transgender people. Drawing on in-depth interview data, it challenges and extends established theorisations of the significance of 'difference' and 'vulnerability' in relation to victimisation. It introduces and emphasises the idea of 'visibility' as a more useful lens through which to understand the systematic harm caused by hate crime victimisation. Through an analysis of complex identities, the article argues that current conceptualisations of 'visibility' do not appreciate the complex, intersectional nature of visibility, which is key in understanding how people navigate their identities in different spaces and contexts.